Analgesic effects of caudal dexmedetomidine versus midazolam combined with bupivacaine on postoperative pain following paediatric infraumbilical surgeries - Oruobu-Nwogu, Ayanate; Aggo, Alfred T.; Johnson, Uyoata U. (International Journal of Research in Medical Sciences, 2022)
Background: There is continued search for an ideal adjuvant necessitated by the limited duration of singleshot caudal block. The study aimed to compare the analgesic effects of caudal 1.5 µg/kg dexmedetomidine versus 50 µg/kg midazolam combined with 0.20% bupivacaine in children. Methods: Following ethical approval and parental consent, 66 American Society of Anesthesiologists (ASA) class I or II children aged 1-6 years were randomized into three groups (A, B, and C) of 22 each. All patients had laryngeal mask airway (LMA) general anaesthesia induced with propofol and maintained with isoflurane in 100% oxygen. Group A received 1 ml/kg 0.20% bupivacaine and 1.5 µg/kg dexmedetomidine (1 ml), B received 1 ml/kg 0.20% bupivacaine plus 50 µg/kg midazolam (1 ml) while C received 1 ml/kg 0.20% bupivacaine and 0.9% normal saline (1 ml), via the caudal space. Pain was assessed using the face, leg, arm, cry, consolability (FLACC) scale. The time to first analgesic request, (TTFAR) was defined as the period from caudal injection to pain score of ≥4. Analgesic was given when FLACC score was ≥4. Results: All 66 children completed the study. The TTFAR was longest in group A (14.4±2.36), followed by group B (12.0±3.69), and shortest in group C (5.6±1.45), p=0.01, with greatest 24 hours analgesic consumption in group C, p=0.01. Conclusions: Caudal dexmedetomidine or midazolam combined with bupivacaine significantly prolonged the analgesic duration, with superiority of dexmedetomidine over midazolam group in analgesic profile.